ANALISIS DETERMINAN KEJADIAN GANGGUAN JIWA PADA REMAJA DI RUMAH SAKIT JIWA DR. H. MARZOEKI MAHDI BOGOR TAHUN 2021 - Afifah Nurfaidah (2022)
Mental disorders in adolescents may have an impact on quality of adolescents in learning, participating, and being a productive members of the society. It is estimated that 10-20% of adolescents worldwide suffer from mental disorders, meaning that from ten adolescents there is one or two of them who suffers from mental disorders. In 2018, 7% suffered from schizophrenia and 6.1% experienced depression. This study aimed at analyzing determinants of mental disorders among adolescents at dr. H. Marzoeki Mahdi Bogor Psychiatric Hospital. This is a cross sectional study by using purposive sampling and collected 114 respondents. Data analysed by using univariate analysis, bivariate with chi square, and multivariate with multiple logistic regression. The results of the bivariate analysis of this study indicate that there is a relationship between the incidence of mental disorders and family income (POR=4.3; 95% CI=1.9-9.7), father's education (POR=2.9; 95% CI=1.2-7 0.0), sex (POR=4.5; 95% CI=2.0-10.1), family history of mental disorders (POR=6.6; 95% CI=1.4-31.2), smoking habits (POR=2.8; 95% CI=1.1-7.2). In multivariate analysis, it was found that a family history of mental disorders is the determinants of mental disorders in adolescents after being controlled by family function, smoking habits, chronic diseases, and father's education (POR=10.5; 95% CI=1.8-60.3).